Cervical cancer cells induce apoptosis of cytotoxic T lymphocytes - Contreras, Diana; Krammer, Peter H. (Journal of immunotherapy, 2000)
The goal of immunotherapy is to eliminate tumors by generating tumor-specific cytotoxic T lymphocytes (CTLs) in patients or by adoptively transferring ex vivo-activated CTLs into patients. Clinical trials have shown that tumor-specific CTLs often disappear before tumors are completely eliminated. In this study, the authors show that CTLs specific for cervical tumor cells undergo apoptosis after they are co-cultured with cervical tumor cells. The established cervical tumor cell lines and cervical cancer tissues express CD95 (Fas/Apo-1) ligand. The tumor cell-induced T-cell apoptosis can be blocked by an inhibitory anti-CD95 (APO-1/Fas) antibody, indicating that tumor cells induce apoptosis of CTLs through CD95-CD95 ligand interaction. Addition of interleukin-2 (IL-2) and IL-7 into the culture rescues the CTL from tumor cell-induced apoptosis. The rescued T cells retain their full antitumor cytotoxicity. These data suggest that human cervical tumor cells might actively downregulate a cellular immune response by inducing apoptosis of specific T cells during immunotherapy. Local use of IL-2 and IL-7 as adjuvants may promote survival of the CTL and, thus, enhance the efficacy of immunotherapy.